Journeyman electrician's review - Richard E. Loyd (Thomson/Delmar Learning, 2005)
Introducing the tried-and-true tool to prepare for and pass professional electrical licensing exams. Now in its 7th edition JOURNEYMAN ELECTRICIAN'S REVIEW: BASED ON THE NATIONAL ELECTRICAL CODE 2011 uses the same easy-to-understand approach and realistic exam questions that spelled success for previous editions but is updated to reflect the very latest edition of the National Electrical Code. Each chapter of this thorough yet concise study guide focuses on a specific topic covered on the journeyman licensing exams including general writing methods over-current protection grounding special equipment and occupancies and more. Practice questions that mimic those seen on actual exams guide you quickly and efficiently to mastery of the most critical skills. With each question a detailed explanation is provided alongside its answer citing specific code references when applicable and offering hands-on practice using the electrical industry's most authoritative reference. Ideal for apprentice trainees students and professionals this book has a versatility that lends itself to learning in apprenticeship type settings as well as self-study